Simulating Reality: An Exploration of Autoethnography, Deconstruction and Reconstruction in Epic Theater Creation - Darius, Nanda; Bagong Pujiono (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
The migration to Tanjungpinang brought the author consciously into a space of simulation. This movement is a 'self-turn away' from the dynamic productivity of the metropolitan city to the quieter rhythm of a small town. In this new environment, the author not only wanders but also integrates into the rhythm of the local community, experiencing time differently. Isolation from the bustle of the metropolis became a deliberate choice, providing distance and space for deep introspection. Using the method of otoethnography and the anthropological insights of Erving Goffman, Richard Schechner, and Augusto Boal, the author interrogates himself and develops a new concept called epic theater work. The epic is not a Brechtian notion that creates a critical distance for reflection and analysis. Rather, it involves the director's fusion of deconstructed and reconstructed realities into an epic theatrical performance with substance. The resulting method of creation offers theater directors a way to discover themselves and their work through certain stages, namely using intuition over conventional knowledge, rejecting traditional plots and structures, acting as the ultimate experimenter, integrating dynamics, deconstructing the script, encouraging engagement and surprise within themselves and the artistic team, and aiming for a surprising and exciting performance.